The Late La Tene culture in central Slavonia (Croatia) - Dizdar, Marko; Potrebica, Hrvoje (2005)
Central Slavonia, which was transversed by important transit routes along the Sava and Drava Rivers, and the Požega Valley, with its graphite deposits, were areas desired by both the Scordisci and Taurisci. Since most of the settlements and necropolises located along the Orljava and Lonđa Rivers in the eastern section of the Požega Valley contain artefacts characteristic of the Scordisci, it is believed that they in fact controlled the area where the Orljava flows out of the valley toward the Sava, which was the best entry into the Požega Valley from the south. The imports of bronze pottery and weapons came from the west along the valley of the Sava River. This transit route went through areas inhabited by the Taurisci, and that is why we should not be surprised by the finds bearing the characteristics of their culture. The third, and so far the least known component of the material culture belongs to the autochthonous Pannonian population, probably the Breuci, who left an indelible trace in Roman historical sources and memoirs. The task of future research is to more clearly define this component.
Projekt MZOS
Projekt MZOS
ENG